The landscape as background for scenic art. Issue 1 (2nd April 2016) - Puigdefàbregas, Bibiana
ABSTRACT: In this article I discuss how the experience of our particular landscapes influences the artistic productions that we offer to the world. From the perspective of the audience, looking at the stage, we like to recognize the diversity of different cultures. This is always a rich, healthy and honest exercise. The problem arises when the particularity of a given culture is hijacked by the state and used to support a nationalistic agenda. I will develop these ideas while using examples from Catalonia since the early twentieth century and from our participation in PQ15.